Process integration of dimethyl carbonate and ethylene glycol production from biomass and heat exchanger network design - Choomwattana, Chayanit; Chaianong, Aksornchan; Kiatkittipong, Worapon; Kongpanna, Pichayapan; Quitain, Armando T.; Assabumrungrat, Suttichai (Chemical Engineering and Processing, 2016)
This work proposed an integrated production process of dimethyl carbonate (DMC) and ethylene glycol (EG) from biomass. The process started with biomass gasification, CO2 separation and CO2 conversion to ethylene carbonate. DMC and EG were produced via transesterification using reactive distillation and extractive distillation. Various key parameters were examined to optimize operating condition focusing on heat consumption. DMC and EG can achieve 99.5 mol% purity. The process can sustain itself without any external heat sources by using biomass combustion, and all performance indicators were considered under the energy self-sufficient conditions. The ratio of biomass fed to the gasifier and the combustor was found to be 0.38:0.62 where the C, H and O atom efficiencies of the process achieved were 35.83, 53.19 and 40.31%, respectively. When employing heat exchanger network, the atom efficiency of the process could be improved (C: 42.49, H: 61.83, O: 45.21), while the ratio of biomass fed to the gasifier and the combustor increased to 0.46:0.54. The energy consumptions were reported by mass allocation as 143 MJ/kg-DMC. Since all energy was supplied by biomass itself, the process was considered as carbon neutral with a fraction of carbon dioxide fixation from biomass into chemicals of 0.31.
Created from Fastlane, Scopus look-up
Keywords: Biomass gasification; Dimethyl carbonate; Ethylene glycol; Process design; Process simulation